PENGARUH PELATIHAN PEMASARAN DALAM MENINGKATKAN MINAT BERWIRAUSAHA ANGGOTA PODAKAN SUMBER REJEKI DI DESA BANGKOK, KEDIRI - Hendrix Putra Extiyangshah; Dhiyan Septa Wihara (Media Mahardhika, 2022)
The motivation behind this research is to find out the marketing training of members of the pokdakan as a source of fortune on the interest in entrepreneurship. To find out the cause and effect in this problem, the researchers used an associative quantitative approach. In this study, there are 2 variables, namely marketing training for the independent variable and then entrepreneurial interest for the dependent variable. All members of the pokdakan source of fortune can be said to be a population and also a sample because there are few members, then everything can be claimed by the population and a sample of 30 people. This study is to determine the cause and effect of whether marketing training has an effect on interest in entrepreneurship, and also uses the SPSS application. After going through SPSS, the X variable affects the Y variable. Its significance value is 0.00 <0.05 and the coefficient of determination which says the independent variable affects the dependent variable is 0.446 or equal to 44.6%. Then the remaining 55.4% is influenced by different elements that are excluded from this review.